Three-dimensional nanoscale characterisation of materials by atom probe tomography. (17th February 2018) - Devaraj, Arun; Perea, Daniel E.; Liu, Jia; Gordon, Lyle M.; Prosa, Ty. J.; Parikh, Pritesh; Diercks, David R.; Meher, Subhashish; Kolli, R. Prakash; Meng, Ying Shirley; Thevuthasan, Suntharampillai
ABSTRACT: The development of three-dimensional (3-D), characterisation techniques with high spatial and mass resolution is crucial for understanding and developing advanced materials for many engineering applications as well as for understanding natural materials. In recent decades, atom probe tomography (APT), which combines a point projection microscope and time-of-flight mass spectrometer, has evolved to be an excellent characterisation technique capable of providing 3-D nanoscale characterisation of materials with sub-nanometer scale spatial resolution, with equal sensitivity for all elements. This review discusses the current state, as of APT instrumentation, new developments in sample preparation methods, experimental procedures for different material classes, reconstruction of APT results, the current status of correlative microscopy, and application of APT for microstructural characterisation in established scientific areas like structural materials as well as new applications in semiconducting nanowires, semiconductor devices, battery materials, catalyst materials, geological materials, and biological materials. Finally, a brief perspective is given regarding the future of APT.